2020
DOI: 10.1017/s0950268820000874
|View full text |Cite
|
Sign up to set email alerts
|

Responding to measles outbreaks in underserved Roma and Romanian populations in England: the critical role of community understanding and engagement

Abstract: Since 2016, the European Region has experienced large-scale measles outbreaks. Several measles outbreaks in England during 2017/18 specifically affected Romanian and Romanian Roma communities. In this qualitative interview study, we looked at the effectiveness of outbreak responses and efforts to promote vaccination uptake amongst these underserved communities in three English cities: Birmingham, Leeds and Liverpool. Semi-structured in-depth interviews were conducted with 33 providers involved in vaccination d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…To this direction, mobile vaccination vans, door -to-door knocking, school or community-based immunization programs and translator services would be very effective in increasing vaccination uptake—and access to health care in general- in this group [ 8 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…To this direction, mobile vaccination vans, door -to-door knocking, school or community-based immunization programs and translator services would be very effective in increasing vaccination uptake—and access to health care in general- in this group [ 8 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies focused on the role of HCWs and their interaction with minority communities. Bell et al [ 55 ] interviewed 33 HCWs involved in vaccination delivery and outbreak management in three cities with large GRT communities that had experienced significant outbreaks. These HCWs reported that improving MMR uptake and properly managing outbreaks at a local level required links with, and an understanding of, underserved communities, as well as strong coordination and robust funding.…”
Section: Resultsmentioning
confidence: 99%
“…Restructuring healthcare delivery via the establishment of Integrated Care Systems and Boards occurred in the month prior to the announcement of the booster campaign. Coordination of responsibilities required adjustment, but was perceived to cause inefficiencies in the local implementation of the campaign, reflecting the management of past measles outbreak responses among Roma and Romanian families in England ( Bell, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%